Implementing and designing a secure information system based on the DSSS gold sequence using MATLAB - Kadhim Hassan Kaittan; Samir Jasim Mohammed (Bulletin of Electrical Engineering and Informatics, 2021)
During study of directly spread spectrum systems, noted that this system uses many types of code to spread data through communication process. There are different types of code sequences available with good correlation properties, they often use pesudo sequence for spreading which is to be less efficient in protecting information from the breaches that attack the communications systems from penetration. In this article gold sequence will use, which is consider better and more complex than the rest of the code sequence (pseudo-noise (PN) sequence, barker code, hadamard code, and others) in terms of the security aspect of the information, thereby it is difficult to detect the information sent in addition to that it is used in code-division multiple access. Design and implement difficult code to protect information in the communication system carried out here by using MATLAB, for sending a binary data and color photo to be sure that this system is working properly with few errors and better information protection than the rest of the other code that is used in direct sequence spread spectrum.